A CASE FOR INTRODUCTION OF NUMERICAL FISCAL RULES IN SERBIAN CONSTITUTION - Begović, Boris; Marinković, Tanasije; Paunović, Marko (Economic Annals, 2017)
The recommendation of numerical fiscal rules in Serbia, presented in this paper, is based on the inherent bias of fiscal policy towards expenditure, and consequently continuous fiscal deficit and excessive sovereign debt. It is recommended that simple and straightforward numeric fiscal rules should be introduced into the Serbian Constitution. There should be two cumulative numerical fiscal rules, the first regarding the ceiling on sovereign debt and the second regarding the ceiling on net new borrowing. Neither of the rules may be violated. The ceiling on the debt level should be prescribed by the Constitution. The ceiling on new net borrowing should depend on the distance of the sovereign debt from the debt ceiling. An illustrative example is provided, with a debt ceiling of 60%. However, the Fiscal Council should specify a specific sovereign debt ceiling as part of the proposed constitutional amendment.